Reducing bottlenecks: professionals’ and adolescents’ experiences with transitional care delivery - Nieboer, Anna P (BioMed Central, 2014)
BACKGROUND: The purpose of this study was to describe the interventions implemented in a quality improvement programme to improve transitional care and evaluate its effectiveness in reducing bottlenecks as perceived by professionals and improving chronically ill adolescents’ experiences with care delivery. METHODS: This longitudinal study was undertaken with adolescents and professionals who participated in the Dutch ‘On Your Own Feet Ahead!’ quality improvement programme. This programme followed the Breakthrough Series improvement and implementation strategy. A total of 102/128 (79.7%) professionals from 21 hospital teams filled out a questionnaire at the start of the programme (T0), and 79/123 (64.2%; five respondents had changed jobs) professionals completed the same questionnaire 1 year later (T1). Seventy-two (58.5%) professionals from 21 teams returned questionnaires at both time points. Of 389 and 430 participating adolescents, 36% and 41% returned questionnaires at T0 and T1, respectively. We used descriptive statistics and two-tailed, paired t-tests to investigate improvements in bottlenecks in transitional care (perceived by professionals) and care delivery (perceived by adolescents). RESULTS: Professionals observed improvement in all bottlenecks at T1 (vs. T0; p < 0.05), especially in the organisation of care, such as the presence of a joint mission between paediatric and adult care, coordination of care, and availability of more resources for joint care services. Within a 1-year period, the transition programme improved some aspects of patients’ experiences with care delivery, such as the provision of opportunities for adolescents to visit the clinic alone (p < 0.001) and to decide who should be present during consultations (p < 0.05). CONCLUSIONS: This study demonstrated that transitional care interventions may improve the organisation and coordination of transitional care and better prepare adolescents for the transition to adult care within a 1-year period. By setting specific goals based on experiences with bottlenecks, the breakthrough approach helped to improve transitional care delivery for adolescents with chronic conditions.